PENGGUNAAN METODE PENEMUAN UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA MATA PELAJARAN MATEMATIKA PADA KONSEP PENJUMLAHAN KELAS II SEMESTER I SDN DOYONG II MIRI KAB. SRAGEN TAHUN PELAJARAN 2015/2016 - Suyatno, Suyatno (Universitas Nusantara PGRI Kediri, 2016)
Abstract: The learning achievement of Mathematics grade II SDN Doyong II for the 2015/2016 school year are not satisfactory because the average student achievement is still below the minimum completeness criteria (KKM). Math is one of the subjects of the most feared by the students.Obstacles may come from teachers and students themselves. Barriers include a lack of teachers can motivate students to be more please Mathematics. Teachers do not understand learning method in accordance with the learning materials. As a teacher should be smart in selecting methods, techniques, and learning models so that teaching and learning can take place with an active, creative, effective, and fun. Average resistance of students, among others: Some students think that mathematics is a subject that is not interesting, difficult, and boring; Math learning process less conducive; Teachers are still often have difficulty in imparting the basic concepts of mathematics to the students, especially the concept of summation of numbers.To improve the competence of students in summing count numbers need to use methods of the invention. By using the